Revitalizing Muslim society through the integration of Islamic and scientific education: a comparative study of the educational thought of Ahmad Dahlan and Wahid Hasyim - Suswanto, Suswanto; Suprapto, Muhammad; Alma'arif, Alma'arif; Sufia, Neng (Jurnal Pendidikan Agama Islam Al-Thariqah, 2026)
This study addresses the persistent dichotomy between religious knowledge and science in Islamic education, which has contributed to intellectual stagnation among Muslims from the colonial period to the contemporary era. The objective of this study is to analyze the concept of Islam-science integration in the thoughts of KH. Ahmad Dahlan and KH. Wahid Hasyim and to examine its relevance in modern Islamic education. This research employs a qualitative-descriptive approach using a library research method, with content analysis applied to primary and secondary sources related to both figures. The findings reveal that KH. Ahmad Dahlan developed an integrative model through modern schooling by combining religious and scientific curricula, while KH. Wahid Hasyim implemented integration within pesantren by incorporating general sciences without eliminating classical traditions. The originality of this study lies in its comparative analysis positioning both figures as representatives of modernist and traditionalist educational paradigms that produce complementary integration models. However, this study is limited to secondary data without empirical field validation. The implication suggests that Islam-science integration should be developed into a contextual and praxis-based educational model that is adaptive to technological advancements while maintaining strong ethical and spiritual foundations.